Analisis Undang-Undang Nomor 50 Tahun 2009 Tentang Pengadilan Agama dalam Penyelesaian Sengketa Ekonomi Syariah dan Relevansinya terhadap Tujuan Hukum Islam (Maqasid Assyari’ah) - Muhammad Romli; Adi Susandi; Ikmal Mumatahaen (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article analyzes Law Number 50 of 2009 concerning Religious Courts in the context of resolving sharia economic disputes and its relevance to the objectives of Islamic law (maqasid al-shari'ah). The main focus of this study is to evaluate the effectiveness of the Law in resolving disputes related to sharia economics and how the implementation of the law is in line with the principles of maqasid al-shari'ah, namely the protection of religion, soul, mind, descendants, and property. Through an analytical approach, this article discusses various aspects of Law Number 50 of 2009, including the structure, competence, and dispute resolution mechanisms regulated in the law. In addition, this article also examines the extent to which the implementation of the Law supports the achievement of maqasid al-shari'ah in the context of sharia economics, as well as the challenges and opportunities faced in the process. This study uses qualitative methods with document analysis and interviews as tools to obtain relevant data. The findings of this study are expected to provide insight into the suitability between laws and regulations and the principles of Islamic law as well as the contribution of religious courts in resolving sharia economic disputes.